“It’s Like the Zombie Apocalypse Here”: Correctional Officer Perspectives on the Deleterious Effects of the COVID-19 Pandemic - Ferdik, Frank (Crime & delinquency, 2025)
Correctional officers are shouldered with important responsibilities designed to reinforce institutional security, yet work under hazardous conditions that can jeopardize their wellbeing. Among the myriad dangers they confront, COVID-19 has now presented itself as an additional threat to officer wellness. Presently little is known about how the coronavirus pandemic has affected officers, or their respective institutions. Semi-structured interview data collected from correctional officers working in a large, urban county jail located in the southeastern United States (N = 21) revealed how COVID-19 significantly disrupted institutional operations, compounded health concerns for officers, and created a climate of confusion over procedures designed to contain spread of the virus. Policy implications are discussed.